Effect of Different Doses of Mangrove Leaf Juice on the Survival of Tilapia Seeds Infected with Parasite Trichodina sp. - Zubair Y Supu; Juliana Juliana; Mulis Mulis (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2020)
This study aims to determine the effect of immersion in a mangrove api-api (Avicennia marina) leaf juice with different doses that affect the survival of tilapia (Oreochromis niloticus) seeds infected with the parasite Trichodina sp. This research is a quantitative descriptive study with 4 treatments and 3 replications. The fish used were tilapia that had been infected with an initial intensity of 205 Trichodina sp. This research was conducted for 7 days. The treatment used was the dosage of mangrove leaf juice and water, where the dosages were A (2.5 gram/liter), B (5 gram/liter), C (7.5 gram/liter) and D (Control). The results showed that giving different doses of api-api leaf immersion had an effect on the survival of tilapia where the use of the mangrove leaf juice at a dose of 7.5 mg/liter gave the best survival results with a percentage of 86.66% and also is a solution dose that can reduce the intensity of Trichodina sp. The results of the calculation of the intensity of Trichodina sp. in treatment A (2.5 gram/liter), namely 30 individuals/head and treatment B (5 gram/liter) 15 individuals/head of treatment C (7.5 gram/liter) the intensity of Trichodina sp. 6 individuals/head. Keywords: Mangrove; api-api; Avicennia marina; tilapia; Trichodina sp.; survival rate.